DIPG-51. ACVR1 MUTATIONS PROMOTE TUMOR GROWTH IN MODELS OF DIFFUSE INTRINSIC PONTINE GLIOMA. (4th December 2020) - Adorno, Jennifer Ocasio; Hover, Laura; He, Chen; Zhu, Xiaoyan; Goldhamer, David; Carcaboso, Angel; Yadavilli, Sridevi; Nazarian, Javad; Baker, Suzanne
Abstract: Mutations in the gene encoding activin A receptor type 1 ( ACVR1 ) are found in approximately 25% of diffuse intrinsic pontine gliomas (DIPGs), a pediatric glioma with 2-year survival rate of less than 10%. ACVR1 mutations frequently coincide with activating PIK3CA or PIK3R1 mutations, indicating a potential cooperative effect of BMP and PI3K signaling in gliomagenesis. We used genetically engineered mice with inducible knock-in of Acvr1 R206H or Pik3ca E545K alleles, such that cre-mediated recombination resulted in expression of the gain of function mutated genes from their endogenous promoters at physiological levels. Cre-mediated deletion in GFAP-CreER;Pik3ca E545K/+ ;p53 cKO mice ( Pik3ca;p53 ) mediated Trp53 deletion and expression of Pik3ca E545K in glial progenitors, and spontaneously induced high-grade glioma (HGG) in mice with complete penetrance. Heterozygous knock-in of the Acvr1 R206H allele accelerated tumorigenesis and impaired survival in Pik3ca;p53 mice ( Acvr1;Pik3ca;p53 ). Transcriptomic analysis of Acvr1;Pik3ca;p53 tumors compared to Pik3ca;p53 littermate controls, as in patient-derived tumors, revealed broad molecular signatures associated with cell fate commitment and chromosome maintenance. Pharmacologic inhibition of ACVR1 was sufficient to impair growth in human patient-derived DIPG cell lines. Together, our studies show that ACVR1 activation promotes tumor growth in spontaneous mouse HGG and patient-derived DIPG cells, suggesting that ACVR1 inhibition may produce a clinically significant therapeutic effect in DIPG.